Mental Readiness Mother Primigravida Prevents Problems and Postpartum Mental Health Problems: Scoping Review - Alya Nursyifa Perwata; Endang Koni Suryaningsih; Cesa Septiana Pratiwi (Journal of Community Health Provision, 2026)
In general, giving birth is one of the fun events, on the other hand there is the presence of new family members in women's lives not always happiness. It needs adjustments to women who experience pregnancy and childbirth. Emotional disorders can be experienced by women after giving birth such as postpartum blues, postpartum depression or postpartum psycholigical. Objective: To map the literature on increasing the mental readiness of primigravida mothers in preventing problems and postpartum mental health problems. The design of this study includes literature review, which is research that discovers theory and analyzes it. Results: Improving the mental readiness of Mother Primigravida preventing postpartum mental health problems, namely increasing mother's knowledge, getting support from her husband, getting social support, and in contact with mental health services. The impact node of the problem and postpartum mental health disorders Mother feels stress, tense relationships, internal rejection, feel worthless, tendencies to commit suicide, feelings of isolation, fear, and mothers feel unable to share their experiences. It is necessary to conduct a more in-depth study on the mental readiness of primigravida mothers using qualitative and quantitative research methods and based on other research methods or designs.